Highly Thermal‐Resistant and Biodegradable Textile Sizes from Glycols Modified Soy Proteins for Remediation of Textile Effluents. Issue 4 (22nd February 2021) - Xing, Bin; Xu, Xiaoyun; Hu, Wenfeng; Ni, Ruiyan; Zhao, Yi
Abstract: Poly(vinyl alcohol) (PVA) sizes are widely used in textile industry due to their excellent sizing properties on synthetic fibers and their blends. However, PVA contains non‐biodegradable chemicals and is a major contributor to environmental pollution related to the textile industry. To overcome this problem, an environmental‐benign and highly thermal‐resistant yarn coating is fabricated from soy proteins, an agricultural byproduct. The soy proteins are chemically modified by glycols having varying chain lengths and number of hydroxyl groups. Compared with the physically modified soy proteins and their sized yarns, coating made from the soy proteins esterified by 1, 4‐butanediol show 91.38% increment in work of rupture at 120 °C and cotton/polyester (65/35) yarns sized by 1, 4‐butanediol esterified soy protein sizes have 39.91% decrease in coefficient of friction. In addition, 1, 4‐butanediol esterified soy sizes have a five‐day biochemical oxygen demand/chemical oxygen demand of 0.476, indicating that the chemically modified soy sizes have high biodegradability in activated sludge. Successful utilization of modified soy sizes can promote large‐quantity applications of soy byproducts, impelling high value addition to agricultural byproducts and sustainability of textile industry. Abstract : Environmentally‐benign and high thermal resistant yarn coating is fabricated from agricultural byproduct soy proteins which is modified by glycols having different chain lengths and number of hydroxyl groups to substitute petro‐based sizes. Biodegradable modified soy sizes show high work of rupture and lower friction coefficient compared to cotton/polyester (65/35) yarns and the physically modified sized yarns.